The effect of consumers’ interest, information access and spending willingness on halal products trustworthiness / Nor Balkish Zakaria …[et al.] - Zakaria, Nor Balkish; Mohamed Yunos, Rahimah; Che Mahmood, Che Faridah; Anita, Rizqa; Said, Jamaliah (Universiti Teknologi MARA Cawangan Selangor, 2017)
Halal certification provides assurance to the consumers particularly the Muslims that the ingredients used and the production processes are according to shariah. The urge of attention to this issue departs from the trust of Muslim consumer to the certification process itself as many fake Halal logo certifications were lodged. Although, many recent studies on Halal issues, nevertheless, much left to be explored on the trustworthiness of Halal for consumers with regard to their purchasing decision. Hence, the purpose of this study is to investigate the effect of consumers’ interest, information access and spending willingness towards the trustworthiness on Halal products. Based on a survey of 167 Malaysian Muslim respondents, the results of this study reveal that trust worthiness of Halal is significantly affected by consumers’ interest on Halal products, their spending willingness and their level of education. This study contributes to the extent literature on Halal trustworthiness among related consumers.